Alterações eletromecânicas do miócito cardíaco na fase aguda da doença de Chagas em modelo murino: papel do óxido nítrico, intereferon-gama e ânion superóxido - Danilo Roman Campos (2011)
Cardiomyopathy observed during infection by the flagellated protozoan Trypanosoma cruzi has unknown mechanism concerning your genesis. Chagas disease is separated in two distinct phases, acute and chronic. In the acute phase it is observed a large number of parasites on blood stream, following activation of immune system which induces severe miocarditis. These alterations in many cases could lead to occurrence of severe arrhythmias, leading to death. Despite of the great importance of Chagas disease in the Latin American, few is known about the mechanisms involved in the establishment of this disease. Based on that, we decided to evaluate the acute phase of Chagas disease in murine model, as well as the influence of strain type in the cardiomyopathy development. Following infection and control of parasitemia with colombian strain of Trypanosoma cruzi, after 81 days, it was not possible to find parasites in the blood stream. The production of MCP-1, IFN-g and TNF-a followed a similar profile of parasitemia curve, however it was possible to see a chronic inflammation at 170 days post-infection (dpi). At first we evaluated the electrocardiogram at 30 dpi. The infection caused an increased in the QRS interval, besides a P wave and QRS complex alternance, with increased heart frequency. Additionally, we observed heart hypertrophy and reduced heart performance at 30 and 15 dpi, respectively, as determined by echocardiography. When we evaluated the isolated cardiomyocyte function, by the shortening index, it was observed a significant reduction in cardiomyocyte shortening at 15, 30 and 45 dpi, in the left and right ventricles (LV and RV). Taking into account the electrocardiographic results, it is possible to realize that there is an electrical remodeling in isolated cardiomyocyte. Thus, we decided to determinate the cellular basis of this phenomenon. In the LV and RV, at 15 dpi we observed a reduced L-type calcium current (ICa,L). In the LV, at 15 dpi, we did not observe any change in the action potential (AP), inward potassium current (IK1) and transient outward fast potassium current (Ito). However, at 30 dpi, in the LV and RV we observed a reduced ICa,L, Ito and an increased time to AP repolarization, as well as and increased in IK1, only in the LV. Besides, we demonstrated that LV has an increased production of nitric oxide at 30 dpi, and inhibition of nitric oxide synthase recovered ICa,L in LV at 30 dpi. Additionally, upstream inhibition in this pathway, the PI3kinase, partially recovered ICa,L. Trying to better understand the molecular basis of cardiomyocyte dysfunction, we evaluated the intracellular calcium dynamics in LF at 30 dpi. However, we did not observe any reduction in calcium transient neither in the SR load. We did not observe alterations in calcium spark frequency and amplitude. In our study we postulate that LV dysfunction is determinated, at least in part, by IFN-g. LV function in isolated myocyte from IFN-g-/- was preserved at 15 and 26-28 dpi. However, RV shortening of myocyte from IFN-g-/- infected mice was reduced depend on infection time. This is an indicative that LV and RV are differentially modulated. We performed some experiments in mice infected with Y strain of Trypanosoma cruzi. Echocardiography revealed a partial and transitory reduction in heart function, however without hypertrophy. When we evaluated ICa,L, Ito and AP in LV in this group, we observed a reduction in ICa,L and Ito and an increase in AP duration at 15 dpi. However, at 30 and 45 dpi we observed either a partial or a complete recovery of all parameters studied, respectively. The mechanism(s) involved in alteration of ICa,L, Ito and AP waveform at 15 dpi was/were attributed to increased production of superoxide, since when we used knockout mice to NADPH-oxidase type 2, we did not observe any alteration . At last, we demonstrated that reduced cholinergic function in heart is not able to induce electrical remodeling basically in the same way as observed in our experimental model. Taking all together, our results demonstrate that the establishment or not of a cardiac chronic phase in Chagas disease, is dependent on Trypanosoma cruzi´s infective strain, which will determinate a chronic or transitory myocarditis.